Estudos fitoquímicos e avaliação do potencial anti-helmíntico da opuntia ficus-indica - Féboli, Aline [UNESP] (2015)
Opuntia fícus-indica (O. ficus), which is native to Mexico and is known as palma forrageira in Brazil, is a species belonging to the family Cactaceae. This plant displays interesting medicinal properties. O. ficus display good nutritional potential is easy to cultivate and is used as feed for small ruminants feed especially in arid areas of northeastern Brazil. Although this plant serves as food for sheep, the literature does not contain any reports on its anthelmintic properties. This paper reports on the ovicidal and larvicidal activity of O. ficus from hydroalcoholic extracts of cladodes and fruits through egg hatch assay (EHA), the larval development assay (LDA), and the larval migration assay (LMIA) using eggs and larvae of gastrointestinal nematodes of naturally infected sheep. For EHA was observed an egg hatch inhibition greater than 90% for both the crude extracts of cladodes and fruits when using a concentration of 50 mg/mL or higher (p < 0.05). Both extracts showed a dose-dependent response with the same value to LD 50 of 9.9 mg/mL. In the LDA, crude hydroalcoholic extract of cladodes showed 98.7 % of inhibition of larval development at 12.5 mg/ mL while the crude hydroalcoholic extract of fruits showed 100% at 50 mg/mL, respectively with an LD 50 of 3.4 mg/mL and 3.7 mg/mL (p < 0.05). In the LMIA, crude extracts showed results greater than 65% inhibition of larval migration at 1.56 mg/mL revealing LD 50 of 0.35 mg/mL and 0.76 mg/mL for the extract of fruit and cladodes, respectively. Fractionation of the crude hydroalcoholic extracts of fruits and cladodes yielded four fractions. Among the fractionated extracts, the residual aqueous and in ethyl acetate extracts of cladodes, in the lowest concentration tested (1.56 mg/mL) resulted in 100% inhibition of larval development. The same result was obtained for n-hexane and aqueous extract of fruits. Therefore, the LD 50 for LDA could not be calculated for these extracts. The ...